ANALISIS PENGARUH BUANGAN LIMBAH DOMESTIK TERHADAP STATUS MUTU AIR DENGAN METODE INDEKS PENCEMARAN (Studi Kasus : SungaiBanger, Kecamatan Semarang Timur) - Novi Melawati; Sudarno Sudarno; Dwi Siwi Handayani (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Banger River is the river with a length of 6.5 km and coverage area of 524,46 ha.The determination status of water quality in Banger River necessary to know how the water pollution in Banger River and recommendations related to the control of pollution river.This research aims to analyze the causes factors changes concentrations of TSS, BOD, COD, DO, pH, Amonia, and Nitrate; calculate the pollution indexon all sampling point inBanger River, and analyze the influence of concentrations of TSS, BOD, COD, DO, pH, Amonia, and Nitrateto water quality status of Banger River.Pollution index were analyzed based on KepMen LH No. 115 in 2003 about the determination the Status of Water Quality Guidelines by taking 5-point sampling and dividing the region segmentation into 4 segments. From this research, a pollution index values are calculated at the BGR point 1 is 8,17; BGRpoint 2 of the resettlement 9,17; BGRpoint 3 of the resettlement 5,17; BGRpoint 4 of the resettlement 7,03 ; and at that BGRpoint5 is 7,48. Based on KepMen LH No. 115 in 2003 about the determination of the Status of Water Quality Guidelines, the value of the IP is at 5,0 < PIj ≤ 10 categorized into polluted medium. So the water quality status at all Banger River the segmentation categorized polluted medium.